Stworzenie świata flory (Rdz 1,11-12) w egzegezie wybranych wczesnochrześcijańskich pisarzy greckich (do końca III wieku) - Szczur, Piotr (Vox Patrum, 2024)
The research purpose of this article is to present and analyze the patristic interpretation of the creation of the world of flora (Gen 1:11-12) in order to show how early Christian writers understood the biblical description. The research was limited to Greek writers active until the end of the third century. First, it was shown how early Christian writers understood the biblical account of the six days of creation. Then the statements on the biblical description of the creation of flora by four early Christian writers were analyzed in detail: Theophilus of Antioch, the anonymous author of the Gnostic treatise De origine mundi, Origen and Pseudo-Clemens. The analysis shows that these thinkers wanted to present a Christian vision of the creation of the world. They emphasized that God is the sole causal cause of the creation of the world, and that He gave the created world a certain shape and purpose for existence. The whole world was brought into existence by God for man’s sake, so that people could use all that had been created and so that they could read the traces of God’s presence in the world. These thinkers showed the richness of God-created elements of the flora world, their order, complexity and beauty. In their view, the world of flora created by God is a kind of „mediator” in the communication between God and man. The analyzed statements of Greek thinkers indicate the anthropocentric orientation of their reflections on the creation of the world, although the biblical text itself is cosmocentric.